2015
DOI: 10.1007/s12664-015-0541-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hypothyroidism in nonalcoholic fatty liver disease in patients attending a tertiary hospital in western India

Abstract: The aim of this study was to assess the prevalence of hypothyroidism in patients with nonalcoholic fatty liver disease (NAFLD). The patients visiting Gastroenterology outpatient clinic between September 2011 and September 2013 at our tertiary care center were investigated for NAFLD. Three hundred controls were selected on the basis of negative ultrasound examination. All patients above 18 years were included. All patients with alcohol intake greater than 20 g/day, HBsAg or anti-HCV positivity, and history of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 29 publications
4
27
0
Order By: Relevance
“…Eleven articles were excluded (4 articles had no comparison group, 3 articles did not report a subject of interest, and 4 articles did not report an outcome of interest). Fourteen observational studies (9 cross-sectional studies [14,15,16,17,18,19,20,21,22], 4 case-control studies [23,24,25,26], and 1 cohort study [27]) involving 7,191 NAFLD patients and 30,003 controls were included in the meta-analysis. Table 1 describes the detailed characteristics and quality assessment of the included studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eleven articles were excluded (4 articles had no comparison group, 3 articles did not report a subject of interest, and 4 articles did not report an outcome of interest). Fourteen observational studies (9 cross-sectional studies [14,15,16,17,18,19,20,21,22], 4 case-control studies [23,24,25,26], and 1 cohort study [27]) involving 7,191 NAFLD patients and 30,003 controls were included in the meta-analysis. Table 1 describes the detailed characteristics and quality assessment of the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 5 studies [14,15,16,20,27] involving 26,454 participants, 6 studies [14,15,16,20,23,27] involving 27,070 studies, and 9 studies [14,15,16,17,18,20,25,26,27] involving 32,347 participants were included in our meta-analyses for assessing the association between NAFLD and subclinical hypothyroidism, overt hypothyroidism, and overall hypothyroidism, respectively. NAFLD was not associated with subclinical hypothyroidism (pooled OR = 0.63, 95% CI: 0.18-2.20, p = 0.47, I 2 = 97%, p heterogeneity <0.01), overt hypothyroidism (pooled OR = 1.37, 95% CI: 0.78-2.41, p = 0.27, I 2 = 81%, p heterogeneity = 0.08), or overall hypothyroidism (pooled OR = 1.21, 95% CI: 0.91-1.61, p = 0.18, I 2 = 72%, p heterogeneity = 0.02) compared with non-NAFLD controls (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We retrieved and evaluated 31 articles in more detail, of which 18 articles were excluded, leaving 13 studies that were eligible for inclusion ( Figure 1). [15][16][17][18][19][20][21][22][23][24][25][26][27] Main characteristics of included studies have been summarized in Table 1 Meta-analysis of the 13 studies found a high correlation between hypothyroidism (including both overt hypothyroidism and subclinical hypothyroidism) and NAFLD (OR=1.48, 95% CI 1.22-1.91, p<0.001)…”
Section: Resultsmentioning
confidence: 99%
“…There is no proven cause-effect relationship between the two conditions. In Indian cohort, patients with NAFLD had higher serum TSH level and lower free thyroxine level than control subjects (12,13). In Germany cohort, there was a confirm association between both subclinical and clinical hypothyroidism and hepatic steatosis (14).…”
Section: Introduction Introductionmentioning
confidence: 99%